ANALISIS PENGARUH PAJAK PENGHASILAN PPH 21 KARYAWAN TERHADAP PENDAPATAN DI WILAYAH DKI JAKARTA - Rahma Andhira Yusup; Candra Sigalingging (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
The focus of this research is to gain an understanding of how the PPh21 individual income contribution rate effects the income of employees in the regions and to evaluate how this tax policy affects the income levels of individuals and groups in the DKI Jakarta Region. The approach applied is quantitative descriptive analysis with descriptive statistical analysis. This approach also examines the characteristics of each approach variable by examining the mean (average), maximum and minimum figures. In statistical analysis there is also the Cronbach alpha technique, which is a method of assessing reliability by comparing the number of one variable with another. If the alpha value is > 0.6 then the data is considered reliable, but if < 0.6 then the data is not reliable. This approach also uses regression. The research results show that the Cronbach alpha value is 0.709, which is higher than the average Cronbach alpha value of 0.6, so this figure can be considered reliable and the research results from simple regression also show a significant effect. This data collection also has a significant impact on DKI Jakarta employees in terms of monthly income tax deductions. Even though this program is not yet complete, it is hoped that in the future this program can reach all workers better and ensure equal distribution of income.